A Silent Voice : Learning to Listen - Book 1 Vol. 1 - Oima, Yoshitoki (London : Kodansha Europe, 2015)
Shoya is a bully. When Shoko, a girl who cant hear, enters his elementary school class, she becomes their favorite target, and Shoya and his friends goad each other into devising new tortures for her. But the childrens cruelty goes too far. Shoko is forced to leave the school, and Shoya ends up shouldering all the blame. Six years later, the two meet again. Can Shoya make up for his past mistakes, or is it too late?
Rated T : Ages 13+
Keywords: Deaf children -- Comic books, strips, etc; Bullying -- Comic books, strips, etc; Bullies -- Comic books, strips, etc; Conduct of life -- Comic books, strips, etc; School children -- Comic books, strips, etc; Teenagers -- Comic books, strips, etc; Comic books, strips, etc. -- Japan; Manga; Manga